A Novel Approach for Secure and Reliable Color Image Authentication and Recovery using Alpha Layer and Secret Sharing - Maher Adel Al Dbsawie; Suleiman Alassly; Hasan Al Jabbouli (Sistemasi: Jurnal Sistem Informasi, 2026)
In the contemporary digital environment, securing digital images against forgery has become a critical necessity, particularly in sensitive domains such as the judiciary, criminal investigations, and communications security. Any manipulation or falsification of legal documents or digital evidence can lead to serious consequences and significant challenges. This study proposes a method for protecting color scanned images and documents by utilizing an invisible component within them, specifically the alpha channel (transparency layer), to embed authentication and recovery data. The process begins by applying a Downsampling operation to the cover image to reduce its size while preserving fine visual details, taking into account the removal of aliasing to achieve the best possible representation of edges and details prior to reduction. Subsequently, 15 secret bit planes are combined to form 4 composite secret bit planes, which are then embedded into the alpha channel. During the recovery phase, these four bit planes are extracted from the alpha channel, from which the original 15 authentication bit planes are reconstructed. The reconstructed data are then matched with the verification data, and in case of any discrepancy, the image is repaired using the embedded authentication data. This approach enables the detection of any tampering and facilitates image recovery if it has been altered or manipulated. One of the key advantages of this method is that it does not affect the visual quality of the host image, as the data are embedded within the added alpha channel. Any attempt to tamper with the image can be detected, and based on the embedded data, the modified or deleted regions can be restored. The proposed method was tested on various types of color scanned images and documents under diverse attack scenarios (content modification attacks and visual quality attacks), demonstrating remarkable effectiveness in preserving image integrity. This technology is particularly important for law enforcement, information security, digital forensics, and any security teams requiring reliable image authentication. The system is also designed to be user-friendly and does not require any specialized hardware, making it practical and suitable for real-world applications.